Health - Discovery Channel School; Discovery Communications Inc. ([Bethesda, Md.] : Discovery Communications Inc., 2003)
This cd-rom features the role of the amygdala and the frontal cortex as they relate to emotional maturity and rational thinking and also explains the importance of diet and good exercise to good health
Teacher's guide in PDF and Microsoft Word format
System requirements : Windows 95/98, pentium processor 100 MHz and above, 16 MB installed RAM, minimum 25 MB free hard disc space, minimum resolution of 640 X 480, 16-bit color, 4 X CD-ROM drive
System requirements : Power PC macintoch at 100 MHz or better, running system 7.6.1 or higher, minimum of 8 MB available RAM, minimum of 25 MB free had disc space, 640 X 480 resolutions, 16-bit color, 4 X multimedia-compliant CD-ROM drive
Keywords: Health -- Juvenile literature; Health behavior -- Juvenile literature; Self-care, Health -- Juvenile literature; Medicine, Preventive -- Juvenile literature